Civil Democratic Islam - Benard, Cheryl; Riddile, Andrew; Wilson, Peter A.; Popper, Steven W. (RAND Corporation, 2023)
In the face of Islam's own internal struggles, it is not easy to see who we should support and how. This report provides detailed descriptions of subgroups, their stands on various issues, and what those stands may mean for the West. Since the outcomes can matter greatly to international community, that community might wish to influence them by providing support to appropriate actors. The author recommends a mixed approach of providing specific types of support to those who can influence the outcomes in desirable ways.